Oklahoma! (United States FoxVideo, 1994)
A love story between a ranch-hand and a farmer's daughter, set in the Oklahoma Territory in the early 1900s.
Adapted from Rodgers and Hammerstein's musical play based upon a dramatic play by Lynn Riggs.
c1955, renewed c1983.
VHS.
Music by Richard Rodgers ; book and lyrics by Oscar Hammerstein II ; screenplay by Sonya Levien and William Ludwig ; produced by Arthur Hornblow Jr., ; directed by Fred Zinneman.
Gordon McRae, Gloria Grahame, Gene Nelson.
Keywords: Love -- Oklahoma -- Drama; Cowboys -- Oklahoma -- Drama; Farmers -- Oklahoma -- Drama; Dance parties -- Oklahoma -- Drama; Oklahoma -- Social life and customs -- Drama